Kompleksowe podejście do zarządzania relacjami z klientami - Nita, Bartłomiej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents the comprehensive approach to customer relationship management. The analysis described in the article can be treated as comprehensive, because it takes into account two different perspectives: operational and strategic. The operational aspect concerns customer profitability analysis and as a consequence appropriate customer cost allocation and furthermore it involves the classification of customer costs (in particular cost to acquire, cost to provide, cost to serve and cost to retain). Thus in the first, part of the paper the methodology of customer cost analysis is presented on the basis of activity-based costing and the proposition of management report that allows to calculate customer profitability is submitted. The strategic aspect relates to customer analysis from the point of view of corporate value creation. Therefore in the second part of the article the essence of customer value is depicted taking into account customer lifetime value. Besides the methods of valuing the customers and different approaches to assessing customer portfolio are examined. Finally the relationship between customer value and corporate value is explained by means of discounted cash flow techniques. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 241-256